Empirical discourse analysis on correlations between exchange rate and exports / Chayongkan Parnornmast, Kittisak Jermsittiparsert and Thanaporn Sriyakul - Parnornmast, Chayongkan; Jermsittiparsert, Kittisak; Sriyakul, Thanaporn (Research Management Institute (RMI), 2013)
The objective of this study focuses on empirically analysing the discourse on the correlations between exchange rate and exports, which has been reproduced constantly and extensively in Thai society by authorities from academic circles and public and private sectors. Hence, this study analyses the time series data of exchange rate and exports by means of advanced statistical methodologies, the regression analysis and Johansen's cointegration test. The regression analysis finds that the exchange rate is negatively correlated to the exports, but Johansen's cointegration test results contrariwise that there is no cointegrating relationship in-between. Therefore, such a claim is not an error made in good faith but another example of domineering discourses enabling the elites to take advantages by disguising them as knowledge and truths, over which the other members in the society dare not to doubt nor dispute.